2020
DOI: 10.1007/s00259-020-05046-9
|View full text |Cite
|
Sign up to set email alerts
|

EANM procedural guidelines for PET/CT quantitative myocardial perfusion imaging

Abstract: The use of cardiac PET, and in particular of quantitative myocardial perfusion PET, has been growing during the last years, because scanners are becoming widely available and because several studies have convincingly demonstrated the advantages of this imaging approach. Therefore, there is a need of determining the procedural modalities for performing high-quality studies and obtaining from this demanding technique the most in terms of both measurement reliability and clinical data. Although the field is rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
68
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 219 publications
(231 reference statements)
0
68
0
1
Order By: Relevance
“…15 O-water PET was defined abnormal in the presence of at least one coronary territory having reduced stress MBF (B2.3 mL/g/min) or reduced MFR (B2.5) based on the previously reported cut-off values. [1][2][3][4] Compared with normal stress MBF or MFR, a substantially higher ICA referral rate of 49% was found among patients with abnormal findings. Out of the 19 patients having reduced stress MBF or MFR referred to ICA, 12 patients subsequently underwent coronary revascularization resulting in actual revascularization rate of 63%.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…15 O-water PET was defined abnormal in the presence of at least one coronary territory having reduced stress MBF (B2.3 mL/g/min) or reduced MFR (B2.5) based on the previously reported cut-off values. [1][2][3][4] Compared with normal stress MBF or MFR, a substantially higher ICA referral rate of 49% was found among patients with abnormal findings. Out of the 19 patients having reduced stress MBF or MFR referred to ICA, 12 patients subsequently underwent coronary revascularization resulting in actual revascularization rate of 63%.…”
mentioning
confidence: 92%
“…15 O-water has favorable kinetics for absolute quantification myocardial blood flow (MBF) that can be presented as parametric maps of stress MBF or myocardial flow reserve (MFR) enabling evaluation of regional perfusion abnormalities. 1 Prospective clinical studies have shown that both stress MBF and MFR assessed by 15 O-water PET have high diagnostic accuracy in the detection of significant CAD defined as an abnormal fractional flow reserve (FFR) in patients with suspected CAD. [2][3][4] In addition to diagnostic performance, clinical value of a diagnostic test depends on its ability to stratify patients at low or high risk of adverse events and impact on choosing subsequent treatment strategy.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] The increasing use of MBF and MFR quantification among multiple hospitals performing Rb-82 PET MPI and the lack of consensus in literature and guidelines on reconstruction protocols has led to a wide variety of temporal sampling protocols that could limit accuracy and data comparison between centers. 6,7 A temporal sampling protocol is used to reconstruct dynamic images. These dynamic images are then used to determine the tracer activity concentration in the blood pool (left ventricle (LV)) and myocardial tissue over time in order to quantify MBF and MFR.…”
Section: Introductionmentioning
confidence: 99%
“…5 Attempts to correct respiratory motion errors have been made with external motion tracking devices and data-driven algorithms but many of these methods are too complicated to be practical. 4 Surprisingly, however, earlier work by Lubberink et al showed that computation of MBF is possible without the need for attenuation correction for 15 O-water PET, owing to the fact that AC affects the overall amplitudes or scale of the time-activity curves and not their time-varying changes in amplitude or shape. 6 This is because 15 O-water MBF quantification models the wash-in and wash-out rates and not the relative uptake in the myocardium.…”
mentioning
confidence: 99%
“…3 Visual interpretable images, however, can be generated either by digital subtraction of the blood pool from the tissue images or by voxel-wise parametric imaging of MBF. 4 For this latter approach, a 1-tissue compartment model based on the clearance or wash-out rate that is proportional to MBF is employed. 3 Attenuation correction (AC) recovers signals in soft tissue surrounded by dense structures and can increase diagnostic yield.…”
mentioning
confidence: 99%